The coastal interface: Lesbos and Anatolia - Evans, A (2013)
This thesis is a regional history of Lesbos and the adjacent regions of Troas and Aiolis in NW Turkey during Greco-Roman antiquity. This area represents a zone of transition between the Mediterranean and inland Asia Minor, and therefore provides us with a case study of how regions which lie at the margins or beyond the theoretical framework of Horden and Purcell's The Corrupting Sea (2000) function. Rather than defining the area of study simply in terms of physical geography, I instead argue that we can identify a region which I term the coastal interface that is characterized by the overlapping and intermingling dynamics of the maritime and terrestrial worlds. This zone of transition can extend out to sea to include nearby islands which are orientated towards the mainland, for example Lesbos in the case of my thesis, or equally it can stretch inland up river valleys or along other routes of communication to places which, although out of sight of the sea, were nevertheless profoundly influenced by their connection to the maritime world. The chapters of the thesis aim to demonstrate that the concept of the coastal interface can help illuminate the social and economic history of communities living within this region, with Chapters 1-3 focusing on the Troad and Chapters 4-7 looking at Lesbos. The subjects covered include Hellenistic Ilion and the koinon of Athena Ilias (Chapter 1), Theophrastos as a source for the social and economic history of the forests of Mt. Ida (Chapter 2), large-scale state-directed horse breeding in the middle Skamander valley (Chapter 3), Mytilene's peraia in coastal Anatolia from the seventh century down to 427 (Chapter 4), Mytilene's minting of billon and electrum coinage in the fifth century (Chapter 5), the refoundation of the Lesbian koinon in the early second century BC (Chapter 6), and the Aiolian aspect of Mytilenaian identity in the first centuries BC and AD (Chapter 7).